A ALIMENTAÇÃO HOSPITALAR MODERNA E A (RE) PRODUÇÃO DO VIVER SOCIAL NO HOSPITAL MIGUEL COUTO EM NATAL (1927-1955) - Mota, André; Silva, Rodrigo Otávio da (História em Revista, 2021)
Este artigo analisa a alimentação no Hospital Miguel Couto na cidade do Natal (RN) entre 1927 e 1955, buscando capturar as representações e práticas alimentares na instituição no momento transicional de um modelo hospitalar caritativo para um modelo de “hospital moderno”, enfocando, no estudo, a materialidade da produção e do consumo alimentar no hospital a partir da abordagem de Jean-Pierre Corbeau e de seu conceito de “sequência do comer”.  Modern hospital food and the (re) production of social living at the Miguel Couto Hospital in Natal (1927-1955)Abstract: This article analyzes food at the Miguel Couto Hospital in the city of Natal (RN) between 1927 and 1955, seeking to capture the institution's food representations and practices at the transitional moment of a charitable hospital model for a “modern hospital” model, focusing, in the study, the materiality of production and food consumption in the hospital based on Jean-Pierre Corbeau's approach and his concept of “eating sequence”.